1994
DOI: 10.1111/j.1467-9507.1994.tb00044.x
|View full text |Cite
|
Sign up to set email alerts
|

The world of parents and peers: coercive exchanges and children's social adaptation

Abstract: The relation among child antisocial behavior, child coercive exchanges with parents and peers, and the social adaptation of middle-childhood-aged boys and girls was investigated. The 374 children were observed during laboratory tasks with their parents and during recess with peers. A covariance model was tested that hypothesized that coercive exchanges with parents and peers would contribute uniquely to a multiple-agent assessment of child antisocial behavior, supporting an ecological view of social developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 29 publications
5
63
0
Order By: Relevance
“…Our results are consistent with previous findings on how mutual hostility unfolds in the family and at school (Snyder and Patterson 1995;Schwartz et al 1997), and between the family and school (Dishion et al 1994;Snyder et al 1994). Although previous studies have shown that adolescents' maladaptive behaviors are transmitted from the home to other settings (Patterson 1986;Schwartz et al 1997), most of these studies have focused solely on home-to-school adjustment.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with previous findings on how mutual hostility unfolds in the family and at school (Snyder and Patterson 1995;Schwartz et al 1997), and between the family and school (Dishion et al 1994;Snyder et al 1994). Although previous studies have shown that adolescents' maladaptive behaviors are transmitted from the home to other settings (Patterson 1986;Schwartz et al 1997), most of these studies have focused solely on home-to-school adjustment.…”
Section: Discussionsupporting
confidence: 94%
“…The coercion model of development suggests that a coercive pattern of socialization begins within the family and may later generalize to relationships outside of the family (i.e., peer relationships), further supporting an antisocial pattern of socialization (Dishion, Patterson, & Griesler, 1994; Patterson, 1982). The confluence model of peer influence builds upon this research and suggests that conventional peers reject children engaging in coercive socialization, limiting coercive children to socialize with other rejected children, also likely to be coercive and/or antisocial (Dishion et al, 1994). Over time, deviant behavior escalates through peer reinforcement of antisocial values, attitudes, and behavior (e.g., deviancy training; Dishion, Duncan, Eddy, Fagot, & Fetrow, 1994; Dishion et al, 1994).…”
Section: Family Influences On Adolescent Delinquency: Setting the Stamentioning
confidence: 99%
“…Two notable risk behaviors that heighten susceptibility for downward assimilation are aggression and rule breaking behaviors. More aggressive youth often have difficulty integrating with their more normatively oriented peers, a form of social rejection that then can encourage friendships and bonding with adolescents more tolerant and encouraging of these behaviors (Dishion, Duncan, Eddy, Fagot, & Fetrow, 1994; Tremblay, Pagani-Kurtz, Mâsse, Vitaro, & Pihl, 1995). Associations with other delinquent youth are strong correlates of aggression and general deviancy, but have also been evidenced to increase the frequency, intensity, and duration of problematic behaviors that only further alienate students from mainstream groups (Copeland-Linder, Lambert, & Ialongo, 2010; Gil & Vega, 2001; Nagin & Tremblay, 2001).…”
Section: Segmented Assimilationmentioning
confidence: 99%